Depression, anxiety disorders, and patterns behaviours in patients with coronary artery disease - Barczyk, Edyta (2006)
The diseases of the circulatory system are the greatest health problem in the world. According to WHO, till 2020, the second place will have taken by depression. The own trial was realized with patients with CAD and depression. The aims of the investigation were to establish the frequency of depression, disorders of anxiety and pattern behaviour A in patients with CAD; characterization the clinical picture of the patients with CAD and depression; the presence the risk factors of the CAD and depression; to establish the diagnostic procedures with the ill patients with the suspicion of depression on cardiological and cardiosurgical departments. The project was realized between November 2002, and June 2004. The patients with CAD, hospitalized in Department of Cardiac and Vascular Diseases and in Department of Cardiac, Vascular Surgery and Transplanthology, Institute of Cardiology, Jagiellonian University Collegium Medicum, participated in this project. 1170 patients entered into the investigation. There were 321 women, and 772 men, from 21 to 89 years. Depression according to Beck scale had 46,1% patients: 59,2% women, and 40,7% men. Psychiatrics established the complete diagnosis of depression in 34,5% women, and 24,1% men.
Keywords: ankiety disorders; coronary artery disease; depression; patterns behaviours